A extensão na Universidade Federal do Tocantins (câmpus de Araguaína): possibilidades de diálogo social e cultural - Sousa, Ianed da Luz (2020)
What are the contributions of the extension actions in the initial formation of teachers that contribute social and cultural dialogues between the university and society? This research problem mobilized us to understand the articulations of participatory methodologies with the extension projects of the Federal University of Tocantins, Campus of Araguaína. In this work, we understand the university, from of a decoloniality perspecitve, in search of the integration of academic cultures and society in order to overcome Eurocentrism, based on the Paulo Freire’s thought, Boaventura de Souza Santos, Catherine Walsh and other authors. The methodology was characterized in a qualitative, exploratory-descriptive approach from triangulation with documentary research and interviews with the three teachers, and coordinators of extension actions. This set of information allowed the identification of three categories of analysis, that is, “Cultural synthesis”: the social tranformation by collabotarion; “Intercultural translation”: against the waste of experience; and Collaborative learning between authors and actors: the social transformation by action. In the analysis process, we understand how complex is the social commitment of the university, but the extension activities scanned demonstrated the horizontal dialogue between university and society, despite the difficulties to be effective in practice, as an institutional policy, proved capable of achieving a humanist and liberating education, including academics, teachers and the community. From the collaborative learning between authors and actors; of recognition of the plurality of knowledge and experiences by coloniality of knowledge problematization it is believed that the university will expand the construction of socially relevant knowledge, recognizing community participation in the process of planning, development, and evaluating of extensionist actions, in the initial formation of teachers, can be transformative for society and especially for the university, as the creator of new knowledge relevant and relevant to society. Thus we emphasize the importance of interdisciplinarity as a promoter of a solidarity dialogue between knowledge and the strong relationship of the university with (co) production, sharing, communication, exchanges and integration of cultures, through extensionist actions.